6x + 14 = 20 + 4x ------ Combine like terms (subtract 4x and 14 from both sides).
2x = 6 --------------------- Divide by 2.
x = 3
-2x+14=20 x=-3
To solve for x, we'd have to know what this expression equals.
if 'g' = minus 3 then 20 + -3 = 17 17 + -3 = 14
y=16 x= -4
-7m + 20 = -17m - 1010m = -30m = -3
balance the equation 3x-x=20-6 3x-x=2x 20-6=14 2x=14 x=7
-2x+14=20 -2x=20-14 -2x=6 -2x/-2=6/-2 x=-3
(20 - x)/5
20 = 400
20
-2x+14=20 x=-3
To solve for x, we'd have to know what this expression equals.
if 'g' = minus 3 then 20 + -3 = 17 17 + -3 = 14
y=16 x= -4
-7m + 20 = -17m - 1010m = -30m = -3
-3 + 9= 6. 6 - 20=-14. Therefore the answer is -14.
11 plus 5-10 plus 20-9 plus 14-10 is equal to 21